6. DESCRIPTION OF THE REALITY SITUATION OF PATIENTS TREATED FOR DYSLIPIDEMIA AT TAY NINH TRADITIONAL MEDICINE AND PHARMACY HOSPITAL IN 2022 (Vietnam Journal of Community Medicine, 2023)
Objectives: To describe the actual situation of patients treated for dyslipidemia at Tay Ninh traditionalmedicine and pharmacy hospital in 2022. Subjects and methods: Cross-sectional description studyon patients treated for dyslipidemia was conducted at Tay Ninh Traditional Medicine and PharmacyHospital from March 2022 to August 2022. Results: Among 183 patients with dyslipidemiasurveyed: the prevalence of dyslipidemia in men (55.7%) was higher than in women (44.3%),age over 60 accounted for the highest rate (61.2%), mainly Kinh ethnic (92%), live in urban areas(62.3%). 74.3% of patients with dyslipidemia were obese, 56.8% did not smoke, 61.2% did notdrink alcohol, 63.4% did not regularly exercise, and 57.4% used fatty foods in meals. 53.6% had ahabit of eating many sweets, 55.7% did not eat much fiber, 69.4% of patients with dyslipidemia hada musculoskeletal disease, 61.7% had cardiovascular disease, and 37.7% had diabetes. Only 44.8%have correct knowledge about dyslipidemia, 51.91% of patients know about traditional medicine’smethods of treating dyslipidemia, know the name of herb that can control and treat dyslipidemia.Conclusion: Promoting communication to raise patients’ awareness about dyslipidemia is necessary.
Keywords: Dyslipidemia, knowledge.